Maintaining Sustainable and Equitable Ecotourism from the Impacts of Over-tourism on the Welfare of Local Communities - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi (Lembaga Dongan Dosen, 2024)
Bali, as a leading ecotourism destination, faces serious challenges due to the impacts of over-tourism that threaten the sustainability of the ecosystem and the welfare of local communities. This study aims to explore the application of good governance, a multifaceted approach, and community-based nature conservation in maintaining sustainable and equitable ecotourism in Bali. Using panel data regression, this study tests three hypotheses: (1) the application of good governance can reduce the negative impacts of over-tourism and improve the sustainability of ecotourism; (2) a multifaceted approach involving ecological, social, and economic dimensions can improve the welfare of local communities and reduce environmental impacts; and (3) nature conservation involving local communities can support the sustainability of the ecosystem and the ecotourism sector. The results of the analysis show that good governance has a significant positive effect on ecotourism sustainability, the multifaceted approach also shows a significant positive relationship, and community-based nature conservation makes a significant contribution to ecosystem sustainability. This study emphasizes the importance of integrating holistic and community-based ecotourism management policies to create more sustainable and equitable ecotourism in Bali.